Diversité de la flore ligneuse à la périphérie du Parc national de Waza (Cameroun) - Evaliste Remi Jiagho; Louis Zapfack; Louis Paul Roger Kabelong Banoho; Moise Tsayem-Demaze; Jeannine Corbonnois; Paul Tchawa (VertigO)
The Waza National Park and its peripheries are part of an ecological unit of the Waza Logone flood plain, located in the far North region of Cameroon. The knowledge of biodiversity, especially plant biodiversity is the basis of the management necessary for the restoration of this environment. This study aims to qualitatively and quantitatively evaluate plant resources in the periphery of the park. The study focuses on a comparative analysis of the eastern part of the Park (dominated by hydromorphic soils rich in clay, river-lake sand and flooded river during part of the year) and the Western part (characterized by the dominance of Planosols and leached soils, made of a mixture of sand and clay river-lake sand). The experimental research carried out consists of transects with variable sizes, horizontal, parallel and equidistant. Data collection was made on 23 transects, with a sampling rate of 0.8 %. On each transect, dendrometric data of all plant species were collected at breast height (1.30 m) or 10 cm from the ground (for species that were less than one meter in height. The qualitative floristic analysis used the APG classification system (Angiosperms Phylogeny Group) III. The floristic survey identified a total of 52 woody species, distributed in 42 genera and 21 families belonging to the Waza National Park periphery. The diversity index (Shannon) is high in the west of the Park. This shows that physical disturbances, although visible in the zone, did not have a strong influence on the diversity of plant species, and that, there is the presence of relatively old, mature and structured stands. On the contrary, this diversity index is low in the eastern part of the park; this indicates a strong physical disturbance of the area, resulting in the dominance of few species. The vertical structure shows that the future stems and the regeneration stems are less represented, with a very big difference as compared to other stems, an indication that the entire ecosystem is in a state of degradation. Several factors are behind the differences between the eastern and the western part of the Park. First, the pedological factors (soil texture, degree of soil aeration etc.). But these are amplified by climatic factors and population growth. Water, present for a longer time during the year in this region on the edge of the Sahel attracts part of the population especially farmers and livestock rearers. The repercussions on the resources are evident. Also, weak conservation services deployment capabilities during certain periods of the year, (period of flooding) promotes illegal harvesting of plant resources both outside and inside the park, while the population pressure and climatic variations influence the ecology of plant species either directly or indirectly.